PENGARUH LITERASI DIGITAL DAN EFEKTIVITAS APLIKASI SIKAD TERHADAP KUALITAS PELAYANAN DAN KEPUASAAN MAHASISWA FAKULTAS ILMU PENDIDIKAN UNIVERSITAS MUHAMMADIYAH JAKARTA - Lestari, Suci Mulya; ,, Iswan; Suryadi, Ahmad (Instruksional, 2020)
This study aims to determine the effect of digital literacy and the effectiveness of the application of Sikad which is an online academic application on the quality of service and satisfaction of students as users. The study was conducted at the Faculty of Education at the University of Muhammadiyah Jakarta with respondents selected by random sampling of 90 students consisting of 5 study programs, namely: PG-PAUD, PGSD, Mathematics, PBSI, and PBI. This research uses a quantitative approach with survey methods and data analysis techniques using path analysis. The results of this study indicate that of the 7 research results, 3 of them are positive and significant, namely: The effect of the effectiveness of the application of the attitude on the quality of service is significant (T hitung> T table = 2.776 > 1.98 and P value <0.05 = 0.006 <0.05); The effect of service quality on user satisfaction is significant (69,969> 1.98 and 0,000 < 0.05); The effect of digital literacy on user satisfaction through significant service quality (2,803 > 1.98 and 0.005 < 0.05).